ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH ON CONSUMER PREFERENCE IN SELECTING RESTAURANT (STUDY: CABAL DINING, JW RESTAURANT AND JUNGLE BEER) - Osvaldo, Derek Patriksen; Pangemanan, Sifrid S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Eating is a daily necessity. According to the hierarchy of needs, a person must fulfill the physiological needs which are food, water, air and shelter. People concentrate on satisfying these needs before turning to higher needs. Consumer purchase decision is the process involved when individuals or groups select, purchase, use or dispose products, services or experience and ideas to satisfy their needs It is important because in understanding customer decision making, we will understand how consumer make the purchase decision, how the process of decision making by customer from searching until selecting the product or service. This research used quantitative method. Quantitative research seeks to quantify the data. The method used in this research is Analytical Hierarchy Process (AHP). AHP is a method for ranking decision alternatives and selecting the best one given multiple criteria. It allows users to assess the relative weight of multiple criteria or multiple options against given criteria in an intuitive manner. Â  Keywords: customer decision making, analytical hierarchy process